Surface and Catalytic Properties of the CuO/AlO System Treated with Different Proportions of ZnO - Gamil A. El-Shobaky; Nabil H. Amin; Sahar A. El-Molla (Adsorption Science & Technology)
The effects of ZnO treatment on the surface and catalytic properties of CuO/Al 2 O 3 were investigated. All the samples studied contained a fixed amount of CuO (13.5 wt%) while the amount of ZnO dopant was varied in the range 0.68–6.46 wt%. The pure and variously doped solids were subjected to heat treatment (precalcination) in the temperature range 400–600°C. The samples obtained were investigated by XRD methods, nitrogen adsorption at −196°C and studies of their catalytic influence on the decomposition of H 2 O 2 at 20–40°C. The results obtained indicated that ZnO treatment of CuO/Al 2 O 3 followed by precalcination at 500°C led to a progressive decrease in the degree of crystallinity of the CuO phase to an extent proportional to the amount of ZnO present in the system. This suggests that such treatment led to a significant decrease in the particle size of the CuO crystallites produced. The BET surface areas of the treated solids increased on increasing the amount of ZnO present in the system. Similarly, the catalytic activity, as expressed in terms of the reaction rate constant for the decomposition of H 2 O 2 , increased on increasing the amount of dopant added to reach a maximum value (ca. 67%) when 1.7 wt% ZnO had been added to the system, and then subsequently decreased on further addition of dopant. It was found that ZnO treatment of CuO/Al 2 O 3 did not modify the activation energy of the catalyzed reaction but rather changed the concentration of catalytically active constituents without changing their energetic nature.